Desarrollo de las destrezas emocionales para la intervención del trastorno disocial en los estudiantes de 8vo año de educación general básica de la Unidad Educativa “Pedro Carbo” en la ciudad de Guaranda. Periodo lectivo 2022-2023. - Haro Cuichán, Génesis Magdalena (2023)
The present project was carried out at Unidad Educativa “Pedro Carbo” in Guaranda city where it has decided to present the following problem: How does the development of emotional skills influence in the intervention of Antisocial personality disorder (ASDP) in eighth level of basic education students? which solution or alternative was to verify Antisocial personality disorder (ASDP) that students have and, therefore more targeted action with emotional skills that motivate them better in their daily lives. Give that, the purpose of this study was to determine the importance of emotional skills and how these influence in eighth level of basic education students’ daily life inside and outside the educational institution of those who has this type of disorder. The methodology used was a mixed approach where it was applied the all data-collection instruments to the population of seventeen students and their parents, one teacher in charge of the classroom and 2 teachers from DECE department. The results were able to verify, evaluate and showed that most of the students have Antisocial personality disorder (ASDP) or behavioral problems, this may be due to the lack of current communication at their homes which leads to the fact that students cannot develop effective communication inside or outside the classroom so they want to resolve their conflicts in an unreasonable way. Through the final evaluation it was possible to understand that the students did not assimilate that their aggressive behavior is known as Antisocial personality disorder (ASDP), which leads us to try to spread knowledge about these topics of interest. Finally, as a conclusion it is needed more talks and role-plays inside the classroom are needed in order to be able to foster empathy, respect, responsibility and affection inside and outside the classroom so that our students will feel free to build the knowledge